1995
DOI: 10.1016/s0006-3495(95)80373-5
|View full text |Cite
|
Sign up to set email alerts
|

Membrane hydration and structure on a subnanometer scale as seen by high resolution solid state nuclear magnetic resonance: POPC and POPC/C12EO4 model membranes

Abstract: The position on a subnanometer scale and the dynamics of structurally important water in model membranes was determined using a combination of proton magic-angle spinning NMR (MAS) with two-dimensional NOESY NMR techniques. Here, we report studies on phosphocholine lipid bilayers that were then modified by the addition of a nonionic surfactant that is shown to dehydrate the lipid. These studies are supplemented by 13C magic-angle spinning NMR investigations to get information on the dynamics of segmental motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
90
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(95 citation statements)
references
References 17 publications
5
90
0
Order By: Relevance
“…The better resolution obtained for MLVs under HR-MAS conditions allows a more complete assignment of MLVs to be obtained with respect to that reported in the literature [25][26][27] Table 2 and Figure 3a). In particular, the good resolution allowed the 1 H chemical shifts of different methylene groups of fatty acids chains, previously [25][26][27] reported as coincident at 1.3 ppm, to be discriminated.…”
Section: Luvs and Mlvsmentioning
confidence: 66%
See 2 more Smart Citations
“…The better resolution obtained for MLVs under HR-MAS conditions allows a more complete assignment of MLVs to be obtained with respect to that reported in the literature [25][26][27] Table 2 and Figure 3a). In particular, the good resolution allowed the 1 H chemical shifts of different methylene groups of fatty acids chains, previously [25][26][27] reported as coincident at 1.3 ppm, to be discriminated.…”
Section: Luvs and Mlvsmentioning
confidence: 66%
“…Other resonances previously reported as coincident [25][26][27] were well separated: for instance, the resonance at 4.30 ppm due to the CH 2 -4 of the choline moiety was separated from that of the glycerol proton 1' at 4.24 ppm and also the resonance at 5.33 ppm due to the olefinic CH -7 of the oleoyl chain from that of the glycerol CH-2 at 5.30 ppm. The 1 H-1 H NOESY map confirmed the assignment obtained through the 1 H-1 H COSY map and gave further information (see Table 2).…”
Section: Luvs and Mlvsmentioning
confidence: 67%
See 1 more Smart Citation
“…After introduction of magic angle spinning (MAS) to NOESY experiments on membranes, not only crosspeaks to headgroup resonances, but also to the methylene groups of lipid hydrocarbon chains were observed (Forbes et al 1988). Volke and Pampel were the first to report that crosspeaks between the lipid 1-palmitoyl-2-oleolyl-sn-glycero-3-phosphocholine (POPC) and water at a concentration of nine water molecules per POPC have negative intensity, compared to positive intensity for all lipid-lipid crosspeaks (Volke and Pampel 1995). The laboratories of Stark and Epand confirmed that crosspeaks between water and lipid headgroups have negative intensity, but the crosspeak to the methylene resonance of hydrocarbon chains was weak and positive (Zhou et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Volke and Pampel were the first to report that cross peaks between the lipid 1-palmitoyl-2-leolyl-sn-glycero-3-phosphocholine (POPC) and water at a concentration of nine water molecules per POPC have negative intensity, compared to positive intensity for all lipid-lipid cross peaks 3 . The laboratories of Stark confirmed that cross peaks between water and lipid head groups have negative intensity, but the cross peak to the methylene resonance of hydrocarbon chains was weak and positive 4 .…”
Section: Introductionmentioning
confidence: 99%